Post-COVID in women after SARS-CoV-2 infection during pregnancy – a pilot study with follow-up data from the COVID-19-related Obstetric and Neonatal Outcome Study (CRONOS) - Backes, Clara; Pecks, Ulrich; Keil, Corinna Nora; Zöllkau, Janine; Scholz, Christoph; Hütten, Matthias; Rüdiger, Mario; Büchel, Johanna; Andresen, Kristin; Mand, Nadine (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Background Pregnant women are at an increased risk of severe COVID-19 and adverse pregnancy outcomes; data on maternal long-term outcome is scarce. We analyzed long-term follow-ups on women who experienced a SARS-CoV-2 infection during pregnancy to evaluate post-COVID symptoms, particularly fatigue, and their association with quality of life (QoL).Methods 773 women who enrolled in the CRONOS registry between April 2020 and August 2021 were contacted for follow-up from December 2022 to April 2023. Data was gathered through a web-based questionnaire. Subsequently, study coordinators matched the follow-up data with the existing CRONOS data.Results 110/773 (14%) women provided data. 20.9% experienced only acute symptoms during their SARS-CoV-2 infection in pregnancy, while 2.7% women experienced symptoms lasting longer than 4 weeks (long COVID). Symptoms lasting longer than 12 weeks (post-COVID) were reported by 63.6% women and occurred more often after severe COVID-19. Fatigue was the most frequently reported symptom (88%), with 55% of women still experiencing it more than one year after initial infection. 76% of women rated their QoL as “good” or “very good”. Women experiencing post-COVID reported a significantly lower QoL.Conclusion This is the first German long-term data on women after SARS-CoV-2 infection during pregnancy, showing a high rate of post-COVID, a persistence of fatigue, and the impact on QoL. Continuous monitoring of pregnant women with COVID-19 is needed to develop comprehensive management strategies.
Keywords: Post-COVID; Fatigue; Quality of life; maternal long-term outcome